(untitled) (Journal Of Educational and Psychological Researches, 2018)
The research addressed the problem of widows that increased recently enormously. The researcher also referred to the perspective of Islam that gave a significant attention for both widows and orphans as powerless groups. Some straightforward example were presented to reflect the actual difficulties that encounter these groups as well as the author proposed number of appropriate ways that mitigate their psychological and physical sufferings such as: the provision of convenience jobs, and the legislation of rule that save their rights. Moreover, the researcher addressed the importance of marrying widows and what these challenges that encounter polygamy in Arab societies, the advantages and disadvantages of polygamy, and discussing all the social, economic, religious, and psychological issues that related to polygamy for both the previous wife and current wife.